A new species of Leucoagaricus (Agaricaceae, Basidiomycota) from Changa Manga Forest, Pakistan - Khalil, Hajra; Ayyub, Misbah; Akram, Aiza; Niazi, Abdul Rehman (Phytotaxa, 2023)
During a study of the genus Leucoagaricus in Pakistan, we collected a putatively new species with a distinct morphology, anatomy and ITS nrDNA profile from Changa Manga, Punjab. The new species is characterized by the presence of reddish brown central squamules on a milk-white background, thick-walled and ellipsoid spores, narrowly sub-cylindrical to subclavate cheilocystidia and cylindrical stipe. A full description, color photographs, line drawings and a phylogenetic tree of the new species are provided.